2004
DOI: 10.1017/s0317167100053968
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogout of the Transverse Atlantal Ligament: An Unusual Cause of Cervical Myelopathy

Abstract: Calcium pyrophosphate dihydrate (CPPD) deposition disease is an inflammatory arthropathy characterized by the deposition of weakly positively birefringent crystals in articular and periarticular structures. It has also been referred to as pseudogout (owing to its clinical similarity to gout) and articular chondrocalcinosis. T h e CPPD crystals are deposited exclusively in joints and bursae, with occasional extension beyond the anatomical confines of the joint. The cervical spine is uncommonly affected, and sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…The diagnosis of fibrocartilage alone at the C1-2 junction is normally not anatomically feasible, given the lack of an intervertebral disc, and as such should raise suspicion of CPPD deposition. These findings were shared by Greisdale and colleagues 10 who observed CPPD crystals deposited in a fibrocartilaginous matrix on histological examination of the surgical mass, and by Ishida et al, 12 who observed chondroid metaplasia in and around the areas of CPPD deposition in 15 patients that could be misdiagnosed as chondrosarcoma or another incorrect pathological entity. Doherty and Dieppe 6 postulated that a transformation of fibroblasts into chondrocytes occurs in the ligamentous tissues followed by production of inorganic pyrophosphate leading to the deposition of CPPD crystal in the collagen or degenerated fibrils.…”
Section: Histological Findingsmentioning
confidence: 80%
See 1 more Smart Citation
“…The diagnosis of fibrocartilage alone at the C1-2 junction is normally not anatomically feasible, given the lack of an intervertebral disc, and as such should raise suspicion of CPPD deposition. These findings were shared by Greisdale and colleagues 10 who observed CPPD crystals deposited in a fibrocartilaginous matrix on histological examination of the surgical mass, and by Ishida et al, 12 who observed chondroid metaplasia in and around the areas of CPPD deposition in 15 patients that could be misdiagnosed as chondrosarcoma or another incorrect pathological entity. Doherty and Dieppe 6 postulated that a transformation of fibroblasts into chondrocytes occurs in the ligamentous tissues followed by production of inorganic pyrophosphate leading to the deposition of CPPD crystal in the collagen or degenerated fibrils.…”
Section: Histological Findingsmentioning
confidence: 80%
“…Other authors 1,3,10 also choose the transoral-transpharyngeal surgical approach, but without posterior stabilization. One of our patients underwent dorsal occipital-cervical fusion months after his ventral decompression due to return of motor weakness, ataxia, and pain; another patient underwent fusion over 1 year later due to the return of pain with neck flexion.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…There are reports of pseudogout causing myelopathy, mainly in the cervical cord,1 2 3 and invasion of pyrophosphate crystals into the ligamentum flavum has also been reported in the cervical spine in the setting of pseudogout,4 5 but there was no vascular involvement in these cases. Kawano et al performed electron microscopy of operative specimens and suggested that pyrophosphate crystals are preferentially deposited in the ligamentum flavum and areas of degenerate disk, as these are relatively mobile structures within the vertebral column 4.…”
Section: Discussionmentioning
confidence: 84%
“…21,32 Any anterior approach that entails a transnasal or transoral/transpharyngeal approach with resection of the odontoid process to access the lesion in elderly patients has been noted to result in a high rate of morbidity, including infection, spinal fluid leak, longer operative time, and frequent need for posterior instrumented stabilization. 2,11,26 Based on a review of the literature, the incidence of postoperative sepsis, cervical infection, or respiratory or cardiac complications was reported in up to 8.3% of patients. 8,23 The literature discussed here pertains predominantly to patients with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%